Metformin: Targeting the Metabolo-Epigenetic Link in Cancer Biology - Cuyàs, Elisabet; Verdura, Sara; Martin-Castillo, Begoña; Menendez, Javier A. (Frontiers in Oncology, 2021)
Metabolism can directly drive or indirectly enable an aberrant chromatin state of cancer cells. The physiological and molecular principles of the metabolic link to epigenetics provide a basis for pharmacological modulation with the anti-diabetic biguanide metformin. Here, we briefly review how metabolite-derived chromatin modifications and the metabolo-epigenetic machinery itself are both amenable to modification by metformin in a local and a systemic manner. First, we consider the capacity of metformin to target global metabolic pathways or specific metabolic enzymes producing chromatin-modifying metabolites. Second, we examine its ability to directly or indirectly fine-tune the activation status of chromatin-modifying enzymes. Third, we envision how the interaction between metformin, diet and gut microbiota might systemically regulate the metabolic inputs to chromatin. Experimental and clinical validation of metformin’s capacity to change the functional outcomes of the metabolo-epigenetic link could offer a proof-of-concept to therapeutically test the metabolic adjustability of the epigenomic landscape of cancer.